Aligning Legal Effectiveness with Children's Interests: A Study of Marriage Dispensation Decisions in Religious Courts of Amuntai - Hidayah, Ahdiyatul; Alaklabi, Mesfer Ali M (JURNAL INDO-ISLAMIKA, 2023)
This article delves into the significance of the legal effectiveness theory in the context of applying the principle for the well-being of children, specifically within the decisions of marriage dispensations in Religious Courts. The focus is on promoting the welfare of children by means of marriage permits, which are legal policies allowing marriages to take place below the legally stipulated age, subject to certain conditions. Emphasizing the principle of the child's best interests in this scenario is crucial, considering the potential impact on the well-being and development of the children involved. This research is grounded in the theory of legal effectiveness, which underscores the efficient and equitable achievement of legal goals. A qualitative approach is employed, involving interviews with Religious Court judges who handle marriage dispensation cases. The findings reveal that the principle of the child's best interests significantly informs the judges' deliberations. Judges endeavor to ensure that marriage dispensations are granted only when deemed the optimal choice for the child's welfare. This study offers a nuanced understanding of how legal effectiveness contributes to safeguarding children's rights and interests within the realm of marriage dispensations. The practical implication of these findings underscores the imperative to continually develop legal policies and court practices that prioritize the interests and welfare of children.